The influence of students' perceptions and motivation on accounting and taxation careers - Carlos Sampaio; Mónica Régio; Jo\~ao Renato Sebasti\~ao (Administrative Sciences, 2024)
Companies depend on the trust and confidence of the general public to thrive. The integrity of financial reporting practices plays a pivotal role in establishing and sustaining stakeholders' confidence. This trust serves as a foundational cornerstone in managerial decision-making processes and in facilitating the active participation of a diverse spectrum of stakeholders within organizational frameworks. Despite its reputation for ethical and transparent conduct, the field of accounting often grapples with a perception of mundanity, particularly among student populations. This study uses a structural equation modeling approach to assess the impact of students' perceptions of the accounting profession on their motivation in academic coursework, using a sample of 92 undergraduate students of accounting and taxation subjects. Additionally, it seeks to investigate how this motivation directly influences their perceptions of future career and how it operates indirectly through their active engagement in accounting and taxation courses. The research findings indicate that students' perceptions of the accounting profession have a direct and positive effect on the perceptions of future career of individuals enrolled in both accounting and taxation courses. This influence is further mediated by the levels of motivation and engagement observed in the academic domain. Moreover, the results highlight the direct and positive influence of students' motivation and engagement in their coursework on their perceptions of future career.
Keywords: 350; accounting; accounting education; accounting profession; structural equation models